2012
DOI: 10.1371/journal.pntd.0001974
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani Develops Resistance to Drug Combinations

Abstract: Drug combinations for the treatment of leishmaniasis represent a promising and challenging chemotherapeutic strategy that has recently been implemented in different endemic areas. However, the vast majority of studies undertaken to date have ignored the potential risk that Leishmania parasites could develop resistance to the different drugs used in such combinations. As a result, this study was designed to elucidate the ability of Leishmania donovani to develop experimental resistance to anti-leishmanial drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 32 publications
5
81
0
Order By: Relevance
“…However, resistance should be avoided. For instance, miltefosine-paromomycin and SbIII-paromomycin combinations lead to resistance in Leishmania donovani (291). The combination of therapeutic arsenals to increase treatment efficiency as well as decrease cure duration and drug resistance is for the moment the most satisfactory strategy, since no vaccine against trypanosomatids has been discovered so far.…”
Section: Resistance and Treatmentmentioning
confidence: 99%
“…However, resistance should be avoided. For instance, miltefosine-paromomycin and SbIII-paromomycin combinations lead to resistance in Leishmania donovani (291). The combination of therapeutic arsenals to increase treatment efficiency as well as decrease cure duration and drug resistance is for the moment the most satisfactory strategy, since no vaccine against trypanosomatids has been discovered so far.…”
Section: Resistance and Treatmentmentioning
confidence: 99%
“…A trial is under way in East Africa to determine the efficacy of miltefosine in combination with SSG and liposomal amphotericin B (7). However, there is concern about the emergence of resistance even for combination therapy (8), since it has been shown that stepwise in vitro selection is an efficient method to obtain resistant lines of Leishmania donovani against all drugs in use today, including amphotericin B (9). Amphotericin B resistance has also been detected in clinical isolates (10).…”
mentioning
confidence: 99%
“…The recommended first-line therapies for visceral leishmaniasis (VL) include: (i) pentavalent antimonials (meglumine antimoniate and sodium stibogluconate), except in some regions in the Indian subcontinent where there are significant areas of drug resistance (2); (ii) the polyene antibiotic amphotericin B; (iii) the liposomal formulation AmBisome; (iv) the aminoglycoside paromomycin; and (v) the oral drug miltefosine. Although the World Health Organization (WHO) (1,3) recently recommended the use of either a single dose of AmBisome or combinations of antileishmanial drugs in order to reduce the duration and toxicity of treatment, prolong the therapeutic life span of existing drugs and delay the emergence of resistance, recent experimental findings have demonstrated the ability of Leishmania to develop resistance to different drug combinations (4).…”
mentioning
confidence: 99%